Blood pressure-related hypoalgesia: a systematic review and meta-analysis. Issue 8 (August 2020) - Makovac, Elena; Porciello, Giuseppina; Palomba, Daniela; Basile, Barbara; Ottaviani, Cristina
Abstract : Objective: Spontaneous or experimentally induced high blood pressure (BP) is associated with reduced pain perception, known as BP-related hypoalgesia. Despite its clinical implications, such as the interference with early detection of myocardial infarction in 'at risk' groups, the size of the association between high BP and pain has not yet been quantified. Moreover, the distinct association between high BP and physiological or psychological components of pain has not yet been considered so far. The aim of this study was to overcome this gap by performing separate meta-analyses on nociceptive response versus quantifiable perceptual measures of pain in relation to high BP. Methods: PubMed and Web of Knowledge databases were searched for English language studies conducted in humans. Fifty-nine studies were eligible for the analyses. Pooled effect sizes (Hedges' g ) were compared. Random effect models were used. Results show that higher BP is significantly associated with lower nociceptive response ( g  = 0.38; k  = 6) and reduced pain perception, assessed by quantifiable measures ( g  = 0.48; k  = 59). Results: The association between BP and pain perception, derived from highly heterogeneous studies, was characterized by significant publication bias. BP assessment, pain assessment, site of pain stimulation, percentage of female participants in the sample, and control for potential confounders were significant moderators. Conclusion: Current meta-analytic results confirm the presence of BP-related hypoalgesia and point towards the need for a better understanding of its underlying mechanisms. Abstract : Supplemental Digital Content is available in the text